2019
DOI: 10.14814/phy2.14101
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐cell excitability and excitability‐driven diabetes in adult Zebrafish islets

Abstract: Islet β ‐cell membrane excitability is a well‐established regulator of mammalian insulin secretion, and defects in β ‐cell excitability are linked to multiple forms of diabetes. Evolutionary conservation of islet excitability in lower organisms is largely unexplored. Here we show that adult zebrafish islet calcium levels rise in response to elevated extracellular [glucose], with similar concentration–response relationship to mammalian β ‐cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
(113 reference statements)
0
16
2
Order By: Relevance
“…In mammals, cx36 encoded gap junctions mediate the majority of the functional coupling between beta cells [29][30][31] . While previous reports have described the lack of beta cell expression of the zebrafish homolog cx35 32 , we found that cx43 is highly expressed in zebrafish beta cells by 100 hpf ( Figure 5A, Figure 5 - Fig. Suppl.…”
Section: Gap Junctions Are Required For Beta Cell Couplingcontrasting
confidence: 76%
“…In mammals, cx36 encoded gap junctions mediate the majority of the functional coupling between beta cells [29][30][31] . While previous reports have described the lack of beta cell expression of the zebrafish homolog cx35 32 , we found that cx43 is highly expressed in zebrafish beta cells by 100 hpf ( Figure 5A, Figure 5 - Fig. Suppl.…”
Section: Gap Junctions Are Required For Beta Cell Couplingcontrasting
confidence: 76%
“…In more recent work, it was reported that photoablation of leader cells abolishes glucose-induced b-cell [Ca 21 ] i oscillations in zebrafish islets (8). However, in other studies the b-cell glucose-induced [Ca 21 ] i oscillations in zebrafish islets were poorly correlated, and thus islets in this species might lack strong gap-junctional coupling (35). It is therefore of interest that connexin-35b, the zebrafish ortholog of connexin-36, is not detected in zebrafish islets (35).…”
Section: Possible Role Of Diffusible Factorsmentioning
confidence: 95%
“…Little change in [Ca 2+ ] activity is observed in the model when removing either those cells with earlier Ca 2+ oscillations (S4 Fig) or those cells with elevated metabolic activity that when hyperpolarized silences islet [Ca 2+ ] (Fig 1,2). However, differences do exist between zebrafish islets and mouse islets which our model is based upon and has been validated against, including islet size, gap junction protein isoform and Ca 2+ dynamics [44,45]. Thus, species differences may account for these observations.…”
Section: Small Populations Of Metabolically Active Cells Are Not Requmentioning
confidence: 99%